National contributions to climate change mitigation from agriculture: allocating a global target - Richards, Meryl B.; Wollenberg, Eva Karoline; Vuuren, Detlef P. van (Informa UK Limited, 2018)
Globally, agriculture and related land use change contributed about 17% of the world’s anthropogenic GHG emissions in 2010 (8.4 GtCO2e yr−1), making GHG mitigation in the agriculture sector critical to meeting the Paris Agreement’s 2°C goal. This article proposes a range of country-level targets for mitigation of agricultural emissions by allocating a global target according to five approaches to effort-sharing for climate change mitigation: responsibility, capability, equality, responsibility-capability-need and equal cumulative per capita emissions. Allocating mitigation targets according to responsibility for total historical emissions or capability to mitigate assigned large targets for agricultural emission reductions to North America, Europe and China. Targets based on responsibility for historical agricultural emissions resulted in a relatively even distribution of targets among countries and regions. Meanwhile, targets based on equal future agricultural emissions per capita or equal per capita cumulative emissions assigned very large mitigation targets to countries with large agricultural economies, while allowing some densely populated countries to increase agricultural emissions. There is no single ‘correct’ framework for allocating a global mitigation goal. Instead, using these approaches as a set provides a transparent, scientific basis for countries to inform and help assess the significance of their commitments to reducing emissions from the agriculture sector.